The real options solution : - Boer, F. Peter (John Wiley & Sons, 2002)
A New Approach to the Valuation of Businesses and Technologies Based on Options Theory. The Real Options Solution presents a practical approach to applying real options analysis that is based on one core insight: all business plans are options. Whether youre a manager or an investor, this straightforward guide offers a proven new approach to the valuation of businesses and technologies based on options theory–the "total value" model. The Real Options Solution outlines a six-step method for applying this model in a high-risk environment, whether you want to evaluate . . . Start-ups, R&D-intensive companies, Bellwether companies, Capital investments, Hypothetical business problems,..